2019
DOI: 10.1017/s1049096519001288
|View full text |Cite
|
Sign up to set email alerts
|

Selecting in or Selecting Out? Gender Gaps and Political Methodology in Europe

Abstract: Studies investigating gender gaps in the doctoral training of political science students have focused so far overwhelmingly on the US context. Although important research within this context has made strides in identifying the persistent challenges to women’s incorporation in political methodology, much remains unknown about whether women and men have different experiences in methods training during their PhD programs. We contribute to this debate by analyzing data from an original survey on the methods-traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Publication and citation gaps matter because they can privilege some substantive questions and methods over others (often quantitative methods in political science; see Teele and Thelen 2017). Women are socialized within these inequalities from the start of their academic journey, with women receiving less quantitative training than men while PhD students (Gatto et al 2020). Gender gaps persist because they are reproduced through the "Matilda effect" where "women's research is viewed as less important or their ideas are attributed to male scholars, even as a field becomes more diverse" (Dion and Mitchell 2019, 312; see also Brown et al 2020;Key and Sumner 2019).…”
Section: The Emerging Ethics Of Care In Political Science and Irmentioning
confidence: 99%
“…Publication and citation gaps matter because they can privilege some substantive questions and methods over others (often quantitative methods in political science; see Teele and Thelen 2017). Women are socialized within these inequalities from the start of their academic journey, with women receiving less quantitative training than men while PhD students (Gatto et al 2020). Gender gaps persist because they are reproduced through the "Matilda effect" where "women's research is viewed as less important or their ideas are attributed to male scholars, even as a field becomes more diverse" (Dion and Mitchell 2019, 312; see also Brown et al 2020;Key and Sumner 2019).…”
Section: The Emerging Ethics Of Care In Political Science and Irmentioning
confidence: 99%
“…Within computational text analysis, and quantitative research methodology in general, women are particularly underrepresented, studies showing a gender gap across levels in these fields. For example Gatto et al (2020) found that women, on average, cover significantly fewer methods courses in their graduate training compared to their male colleagues, and that women are more likely than men to complete qualitative methods courses. Barnes (2018) shows that women are less likely to be lecturers in quantitative methods courses.…”
Section: The Matilda Effectmentioning
confidence: 99%
“…Barnes (2018) shows that women are less likely to be lecturers in quantitative methods courses. Furthermore, while Gatto et al (2020) also found that when women do participate in methods training they show similar levels of method employment as their male colleagues, Shannon (2014) and Esarey (2018) found that even when women do use the same methods as men, they are less likely to characterize themselves as methodologists. This echoes findings from Morrow-Jones and Box-Steffensmeier (2014) and Shannon (2014) that women's self-evaluation of math-related qualifications tends to be lower than men's, even when they outperform them.…”
Section: The Matilda Effectmentioning
confidence: 99%
“…Yet, building upon studies of gender in the discipline (e.g. Gatto et al 2020;Teele and Thelen 2017), we argue that gendered experiences are the likely culprit for existing differences between men and women in the field; i.e. that women are less likely to uptake CTAM methods, even if it would further their careers, if they believe they lack understanding of the methods and tools.…”
Section: Introductionmentioning
confidence: 99%
“…What makes this worrisome is that this literacy is less widespread among groups who are already underrepresented in academia anyway. Gatto et al (2020) show that different demographic groups employ quantitative methods to a similar degree, yet, be it due to a lack of confidence or due to how courses are taught and by whom, non-White PhD students in particular cover significantly fewer methods courses in their doctoral training. What seems even more baffeling is that women as well, even the ones who have similar socioeconomic backgrounds to their male counterparts, appear more hesitant to engange with methodological and technical training.…”
Section: Introductionmentioning
confidence: 99%